2019
DOI: 10.1111/ajt.15496
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes of deceased donor renal transplants of HCV uninfected recipients from HCV seropositive nonviremic donors and viremic donors in the era of direct-acting antivirals

Abstract: The United States opioid use epidemic over the past decade has coincided with an increase in hepatitis C virus (HCV) positive donors. Using propensity score matching, and the Organ Procurement Transplant Network data files from January 2015 to June 2019, we analyzed the short-term outcomes of adult deceased donor kidney transplants of HCV uninfected recipients with two distinct groups of HCV positive donors (HCV seropositive, nonviremic n = 352 and viremic n = 196) compared to those performed using HCV uninfec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…There was no significant difference in overall graft survival or patient mortality. Further, the KDPI score was numerically lower than would historically be expected of HCV‐positive donors, which is impressive especially as HCV status is a component in the KDPI score . Similarly, the median KDPI score among patients in our series of HCV NAT (+) recipients was 52%, which was not significantly different from the median KDPI among recipients of HCV NAT (−) organs at our institution during the same time period (45%).…”
Section: Discussionmentioning
confidence: 39%
See 2 more Smart Citations
“…There was no significant difference in overall graft survival or patient mortality. Further, the KDPI score was numerically lower than would historically be expected of HCV‐positive donors, which is impressive especially as HCV status is a component in the KDPI score . Similarly, the median KDPI score among patients in our series of HCV NAT (+) recipients was 52%, which was not significantly different from the median KDPI among recipients of HCV NAT (−) organs at our institution during the same time period (45%).…”
Section: Discussionmentioning
confidence: 39%
“…Even among these patients, the persistence of HCV infection post‐transplantation was associated with poor outcomes and led to worse post‐transplant survival . However, the advent of highly effective direct‐acting antiviral therapy (DAAs) has led to post‐transplantation HCV cure rates exceeding 95%, and with it, a negation of the ill effects of HCV previously seen in both LT and KT recipients . A number of clinical trials, along with data from the HCV‐TARGET cohort, have demonstrated the efficacy and safety of the use of these agents in the post‐transplant setting .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single‐center studies have utilized HCV antibody positive and viremic donors for RT with good short‐term outcomes. A recent national registry analysis by our group confirms excellent short‐term outcomes for such transplants …”
Section: Introductionmentioning
confidence: 53%
“…One UNOS study of Ab+/NAT− kidneys concludes that if such kidneys are considered to be HCV‐, their survival would be comparable to the matched non‐HCV‐infected kidneys, less likely to be classified as KDPI > 85%, and the risk of DGF was significantly lower when compared to non‐HCV kidneys . A recent companion study also confirms similar or superior short‐term outcomes from transplantation with HCV+ kidneys . Hence, some authors even question the need for including HCV Ab result with donor offers and KDPI calculations and recommend uniform utilization of NAT status alone …”
Section: Discussionmentioning
confidence: 99%